Result of Percutaneous Release of Trigger Thumb: A Prospective Study - Onta, Pratyenta Raj; Thapa, Pabin; Thapa, Upendra Jung; Sapkota, Krishna; Ranjeet, Niraj (Nepal Journal of Medical Sciences, 2021)
Introduction: Trigger thumb is a common disorder characterized by pain, snapping, and locking of fingers. It usually affects the ring and thumb finger. The treatment of trigger thumb varies according to the grade of triggering. Open surgical release of A1 pulley in trigger thumb is a widely accepted treatment method having its complications like scar mark, pain at the incision site, joint stiffness, and digital nerve injuries. The percutaneous release does have good results in recent studies. It is an easy daycare procedure with low complications. Methods: This study includes 28 patients with trigger thumbs who underwent percutaneous release. Patients were followed up for 6 months duration. Results: There were 30 patients included in the study, only 2 patients required open release so we had an overall 93.33% success rate of percutaneous release. There was no clinical evidence of complications and nerve injury. Conclusion: The percutaneous release is a safe and effective outpatient procedure in patients with trigger thumbs.